Establishment of Gene Copy Number–Specific Normal Ranges for Serum C4 and Its Utility for Interpretation in Patients With Chronically Low Serum C4 Concentrations - Margery-Muir, Audrey; Wetherall, John; Castley, A.; Hew, M.; Whidborne, R.; Mallon, D.; Martinez, P.; Witt, C. (John Wiley & Sons, Inc., 2014)
Objective - To establish gene copy number (GCN)–specific normal ranges for serum C4 genes and to determine their utility with respect to the interpretation of chronically low serum C4 concentrations in patients with clinically quiescent systemic lupus erythematosus (SLE). Methods - C4 serum concentrations were estimated by automated turbidimetry, and C4 GCNs were determined using the TaqMan real-time polymerase chain reaction (PCR) analysis in 184 unselected individuals and in 10 patients with type 1 diabetes mellitus (DM) who were selected for the presence of only 2 copies of the C4 gene. C4 GCNs were also determined in 11 patients with clinically quiescent SLE who had chronically low serum C4 concentrations. Results - A total of 33% of the variation in serum C4 concentrations could be accounted for by both C4A and C4B GCNs (R2 = 0.30, P ≤ 0.0001). There was a median of 2 gene copies at the C4A locus (53.8%) and 2 at the C4B locus (58.7%). The median total number of C4 genes was 4 (55.4%). C4 GCN-specific normal ranges were established. A chronically low serum C4 concentration was explained by a low C4 GCN in 3 of 11 patients tested. Conclusion - This study establishes the feasibility of establishing C4 GCN-specific normal ranges using the TaqMan real-time PCR assay. Chronically low serum C4 concentrations in SLE patients are sometimes explained by low C4 GCNs.